2011
DOI: 10.1145/2049697.2049702
|View full text |Cite
|
Sign up to set email alerts
|

New Constructive Aspects of the Lovász Local Lemma

Abstract: The Lovász Local Lemma (LLL) is a powerful tool that gives sufficient conditions for avoiding all of a given set of "bad" events, with positive probability. A series of results have provided algorithms to efficiently construct structures whose existence is non-constructively guaranteed by the LLL, culminating in the recent breakthrough of Moser and Tardos [2010] for the full asymmetric LLL. We show that the output distribution of the Moser-Tardos algorithm well-approximates the conditional LLL-distribution, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
190
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(195 citation statements)
references
References 44 publications
3
190
0
Order By: Relevance
“…Some extensions of the LLL, such as the Moser-Tardos distribution bounds shown in [16], the cluster-expansion LLL criterion [9] and its connection to the Moser-Tardos algorithm [32], or the partial resampling of [18], follow almost immediately here. There are a few extensions which require slightly more discussion.…”
Section: The Constructive Lll For Permutationsmentioning
confidence: 86%
See 2 more Smart Citations
“…Some extensions of the LLL, such as the Moser-Tardos distribution bounds shown in [16], the cluster-expansion LLL criterion [9] and its connection to the Moser-Tardos algorithm [32], or the partial resampling of [18], follow almost immediately here. There are a few extensions which require slightly more discussion.…”
Section: The Constructive Lll For Permutationsmentioning
confidence: 86%
“…See [16] for the proof of this for the ordinary MT algorithm; the extension to the Swapping Algorithm is straightforward.…”
Section: Comparison With the Approaches Of Achlioptas And Iliopoulos Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In very recent work Moser and Tardos [30] and Haeupler et al [31] have shown how to make this result constructive in the sense that if P r[E i ] ≤ x i Π Ej adj. to Ei (1 − x j ) for all i they obtain a randomized algorithm that with high probability sets the base random variables such that no bad event occurs.…”
Section: Lovász Local Lemmamentioning
confidence: 99%
“…This even holds for another special case called unrelated graph balancing, where each job has (possibly different) finite processing times on at most two machines [6,26]. Configuration LPs have also been studied extensively for the max-min version of the problem [2,3,8,11,17,26], which has become known as the Santa Claus problem.…”
Section: Introductionmentioning
confidence: 99%